Effect of Prolonged Strenuous Exercise on Endothelial Function in Non-Elite Runners (2010)
result in an acute depression in endothelial function. However, little is known about the effect of this type of exercise in non-elite runners. Objective: To determine the impact of prolonged strenuous exercise on endothelial function in nonelite runners.